MODEL PENDIDIKAN AKHLAK KARIMAH DAN LIFE SKILL DI MI PLUS AL-ISLAM DAGANGAN MADIUN - Anggi Eka Cahyati; Katni Katni; Ayok Ariyanto (TARBAWI:Journal on Islamic Education, 2020)
This research is conducted to aim at knowing the  noble character and life skill education model, supporting and inhibiting factors of  noble character and life skill education in MI Plus Al Islam  Dagangan Madiun. In the teaching process, this school not only looking at how far students master the materials but including all aspects such as religious aspects, independent, etc. Noble Character and Life Skill instilled by practices in school. In this research, author uses a qualitative method with subjects are headmaster, teachers, and students. For data collecting, the author using observation, interviews, and document analysis method by data reductions, framing data and conclusion stages. The results of this research are (1) Nobel character education model in MI Plus Al-Islam Dagangan implemented in various methods, there arecultivation method, practices, reward and punishments; (2) Life Skill education process with some extra activities to develop student’s independent. These activities such as gymnast, art and religious activities intended for students to excel in non-academic fields; (3) Supporting factors area leader with great religious integrity and skill, and good feedbacks from parents as a power in supporting noble character and life skill education of MI Plus Dagangan Madiun. The inhabitant factors are ignorance of parents in additional tuition for school activities and weak parental control outside school.